Adaptive Strategic Management in Sustainable Tourism Governance: Cross-Sector Collaboration in Pangandaran, Indonesia - Nanang Suparman (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This study examines the urgency of adaptive strategic management in sustainable tourism governance in Pangandaran Regency, Indonesia, where high visitor flows, coastal safety risks, retribution reform, and environmental pressures challenge conventional destination management. The study aims to analyze how adaptive strategic management is implemented through cross-sector collaboration in responding to visitor pressure, safety risks, retribution governance, and coastal sustainability. The conceptual framework integrates adaptive strategic management, collaborative governance, and sustainable tourism governance. Using a qualitative case study approach, the research analyzes open-source data, including official statistics, regional regulations, government information, credible news reports, and relevant scholarly literature published no later than 30 December 2024. The findings show that Pangandaran’s governance response combines regulatory adjustment, visitor-flow control, beach safety operations, emergency services, environmental action, and multi-actor coordination. The study argues that sustainable coastal tourism requires adaptive governance capacity that links fiscal accountability, public service readiness, risk management, and environmental stewardship effectively.